Isopropylammonium halidometallates. I. [CoX4]2−·X− (X = Cl, Br), ZnCl42−, and [ZnCl3−]n salts - Josh Birke; Tu Nguyen; Marcus R. Bond (Acta Crystallographica Section E: Crystallographic Communications)
An exploration of the isopropylammonium (IPA+) metal halide structural space is conducted, initially, for cobalt(II) and zinc(II) halides as a counterpart to the more extensively studied metal halide systems containing the isomeric trimethylammonium cation. For cobalt(II) halides, the only compound obtained from slow evaporation of acidic aqueous solutions of isopropylammonium halide and cobalt(II) halide is (IPA+)3CoX4·X (X = Cl, Br), namely, tris(isopropylammonium) tetrachloridocobaltate(II) chloride, (C3H10N)3[CoCl4]Cl, and tris(isopropylammonium) tetrabromidocobaltate(II) bromide, (C3H10N)3[CoBr4]Br, regardless of the starting stoichiometric ratio of (IPA+)X:CoX2. These structures consist of isolated tetrahedral CoX42− complexes and X− ions separated by IPA+ cations. One IPA+ cation hydrogen bonds to two complexes and to two halide ions to produce clusters. These clusters form stacks with hydrogen bonding from the remaining IPA+ cations linking the stacks into a tight, three-dimensional network. A 2:1 molar ratio of (IPA+)Cl and ZnCl2 under similar growth conditions readily yields crystals of bis(isopropylammonium) tetrachloridozincate(II), (C3H10N)2[ZnCl4] or (IPA+)2ZnCl4, consisting only of IPA+ cations and isolated ZnCl42− tetrahedra. This despite the expectation of common structural chemistry for the similarly sized Co2+ and Zn2+ ions with 51 known isostructural A2CoCl4 and A2ZnCl4 compounds out of 54 for the same monopositive A cation. Growth from a 1:1 ratio of (IPA+)Cl:ZnCl2 yields crystals of poly[isopropylammonium [[dichloridozincate(II)]-μ-chlorido]], {(C3H10N)[ZnCl3]}n or (IPA+)ZnCl3, in which parallel chains of corner-sharing ZnCl4 tetrahedra are separated by IPA+ cations. This unusual zinc(II) halide chain structure has previously been observed only in [YCH2(CH3)3N]ZnCl3 salts (Y = H, halogen). In contrast to these known compounds, which are found in polar orthorhombic space groups, the structure reported here is in orthorhombic Pbca.